Graphene enriched with pyrrolic coordination of the doped nitrogen as an efficient metal-free electrocatalyst for oxygen reduction - Unni, SreeKuttan M.; Devulapally, Saikrishna; Karjule, Neeta; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
We report an efficient template-free synthetic route for the preparation of mesoporous nitrogen-doped graphene (NGE) containing a high weight percentage of pyrrolic nitrogen, good specific surface area and comparable electrochemical oxygen reduction activity as that of the state-of-the-art 40 wt% Pt/C catalyst. The desired coordination of nitrogen in the carbon framework of graphene has been conceived by a mutually assisted redox reaction between graphene oxide (GO) and pyrrole, followed by thermal treatment at elevated temperatures. NGE exhibits a high surface area of 528 m(2) g(-1) and a pore diameter of similar to 3 to 7 nm. The heat treatment temperature plays a pivotal role in establishing the desired pyrrolic coordination of nitrogen in graphene for the electrochemical oxygen reduction reaction. The NGE sample obtained after heat treatment at 1000 degrees C (NGE-1000) has 53% pyrrolic nitrogen content compared to the similar samples prepared by treating at low temperatures. Most importantly, NGE-1000 has displayed a significantly low overpotential for oxygen reduction with the onset potential very closely matching that of the commercial 40 wt% Pt/C. It is noteworthy that the reaction involves the desired 4 electron transfer as observed in the case of the Pt based electrocatalysts, leading to a significantly high kinetic current density of 6 mA cm(-2) at -0.2 V. Moreover, the fuel tolerance and durability under the electrochemical environment of the NGE catalyst is found to be superior to the Pt/C catalyst.

Graphene oxide sheathed ZIF-8 microcrystals: engineered precursors of nitrogen-doped porous carbon for efficient oxygen reduction reaction (ORR) electrocatalysis - Thomas, Minju; Illathvalappi, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, Abdul Azeez Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ACS Applied Materials & Interfaces, 2016)
Nitrogen containing mesoporous carbon obtained by the pyrolysis of graphene oxide (GO) wrapped ZIF-8 (Zeolitic Imidazolate Frameworks-8) micro crystals is demonstrated to be an efficient catalyst for the oxygen reduction reaction (ORR). ZIF-8 synthesis in the presence of GO sheets helped to realize layers of graphene oxide over ZIF-8 microcrystals and the sphere-like structures thus obtained, on heat treatment, transformed to highly porous carbon with a nitrogen content of about 6.12% and surface area of 502 m(2)/g. These catalysts with a typical micromeso porous architecture exhibited an onset potential of 0.88Vvs RHE in a four electron pathway and also demonstrated superior durability in alkaline medium compared to that of the commercial Pt/C catalyst. The N-doped porous carbon derived from GO sheathed ZIF-8 core shell structures could therefore be employed as an efficient electrocatalyst for fuel cell applications.
Keywords: alkaline fuel cell; graphene oxide; N-doped carbon; oxygen reduction reaction; porous carbon; ZIF-8

Grafoil-scotch tape-derived highly conducting flexible substrate and its application as a supercapacitor electrode - Soni, Roby; Raveendran, Alka; Kurungot, Sreekumar (Nanoscale, 2017)
Development of flexible supercapacitors is limited by the availability of flexible and durable conducting substrates; a conducting and cheap substrate for the active material deposition is essential for breakthrough progress in this direction. In this report, a highly flexible, conducting, and cheap substrate is prepared by simple stick and peel-off method involving Scotch tape and Grafoil. A Grafoil-Scotch tape derived flexible substrate exhibits a sheet resistance of 7 Omega square(-1) along with a high degree of flexibility and durability. Moreover, its properties are further enhanced by the anodization in order to increase the hydrophilicity and surface area. The substrate is highly thin with a thickness of just 74 mu m. Its practical utility has been demonstrated by electrodepositing MnO2 as an active material and, thereafter, fabricating a solid-state flexible supercapacitor. The fabricated device exhibits high capacitance retention under bent (99%) and twisted (98%) conditions along with a low ESR of 7 Omega.

Glycine-induced electrodeposition of nanostructured cobalt hydroxide: a bifunctional catalyst for overall water splitting - Shilpa, Nagaraju; Nadeema, Ayasha; Kurungot, Sreekumar (ChemSusChem, 2019)
Herein, an interconnected alpha-Co(OH)(2) structure with a network-like architecture was used as a bifunctional electrocatalyst for the overall water splitting reaction in alkaline medium. The complexing ability of glycine with a transition metal was exploited to form [Co(gly)(3)](-) dispersion at pH 10, which was used for the electrodeposition. High-resolution TEM, UV/Vis-diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy were used to confirm that the as-synthesized materials had an alpha-Co(OH)(2) phase. The electrocatalytic oxygen and hydrogen evolution activity of the glycine-coordinated alpha-Co(OH)(2) was found to be approximately 320 and 145 mV, respectively, at 10 mA cm(-2). The material required approximately 1.60 V (vs. reversible hydrogen electrode; RHE) to achieve the benchmark of 10 mA cm(-2) for overall water splitting with a mass activity of approximately 63.7 A g(-1) at 1.60 V (vs. RHE). The chronoamperometric response was measured to evidence the stability of the material for overall water splitting for up to 24 h. Characterization of the catalyst after the oxygen and hydrogen evolution reactions was performed by XPS and showed the presence of a Co-II/Co-III oxidation state.
Keywords: cobalt; Electrochemistry; heterogeneous catalysis; Hydrogen; water splitting

Graphene-modified electrodes for sensing doxorubicin hydrochloride in human plasma - Chekin, Fereshteh; Myshin, Vladyslav; Ye, Ran; Melinte, Sorin; Singh, Santosh K.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (Analytical and Bioanalytical Chemistry, 2019)
Doxorubicin (DOX), an anthracycline molecule, is currently one of the most widely used anticancer drugs in clinics. Systematic treatment of patients with DOX is known to be accompanied by several unpleasant side effects due to the toxicity of the drug. Thus, monitoring of DOX concentration in serum samples has become increasingly important to avoid side effects and ensure therapeutic efficiency. In this study, we discuss the construction of a disposable electrochemical sensor for the direct monitoring of DOX in clinical blood samples. The sensor is based on coating a gold electrode in a flexible integrated electrode construct formed on polyimide sheets using photolithography, with nitrogen-doped reduced graphene oxide (N-rGO) suspended in chitosan. Under optimized conditions, a linear relationship between the oxidative peak current and the concentration of DOX in the range of 0.010-15M with a detection limit of 10nM could be achieved. The sensor was adapted to monitor DOX in serum samples of patients under anticancer treatment.
Keywords: Disposable electrodes; doxorubicin; Nitrogen-doped reduced graphene oxide; Serum